Analysis of Turtle Conservation Activities Effectiveness on Kelapa Dua Island, Kepulauan Seribu - Gulo, Graciella Stevani; Tumuyu, Sri Setiawati; Patria, Mufti Petala (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractThe exploitation of turtles has resulted in a decline in the turtle population. The relocation of turtle eggs from nesting habitats is a widely accepted conservation practice. This research aims to analyze the effectiveness of turtle conservation activities on Kelapa Dua Island. The study adopts a mixed-methods approach, collecting primary data through field observations and interviews and secondary data from the Kepulauan Seribu National Park Office (BTNKpS). The collected data includes information on turtle nest monitoring activities, turtle preservation techniques, and the hatching success rate. The research results show that the hawksbill turtle (Eretmochelys imbricata) is the most commonly found turtle species. The average hatching success rate over the past six years is 71.98%. This value can still be optimized to reach 80% by establishing hatcheries on the nesting islands or islands near the nesting sites. Through this strategy, monitoring can be conducted more regularly, the turtle egg relocation process can be carried out relatively quickly, and vibrations or shocks to the turtle eggs during transportation can be minimized, thus increasing the hatching success rate. Regular monitoring of the environmental conditions of the artificial nests, including temperature, pH, and humidity, is also essential to improve the hatching percentage.AbstrakEksploitasi penyu telah menyebabkan penurunan populasi penyu. Relokasi telur penyu dari habitat penetasan adalah praktik konservasi yang umum diterima. Penelitian ini bertujuan untuk menganalisis efektivitas kegiatan konservasi penyu di Pulau Kelapa Dua. Studi ini mengadopsi pendekatan metode campuran, mengumpulkan data primer melalui observasi lapangan dan wawancara serta data sekunder dari Balai Taman Nasional Kepulauan Seribu (BTNKpS). Data yang terkumpul meliputi informasi tentang kegiatan pemantauan sarang penyu, teknik pelestarian penyu, dan tingkat keberhasilan penetasan. Hasil penelitian menunjukkan bahwa penyu sisik (Eretmochelys imbricata) merupakan spesies penyu yang paling banyak ditemukan. Tingkat keberhasilan penetasan rata-rata selama enam tahun terakhir adalah 71,98%. Nilai ini masih bisa dioptimalkan hingga mencapai 80% dengan mendirikan hatchery di pulau-pulau peneluran atau pulau-pulau yang berdekatan dengan lokasi peneluran. Melalui strategi ini, pemantauan dapat dilakukan lebih rutin, proses relokasi telur penyu dapat dilakukan dengan relatif cepat, dan getaran atau benturan pada telur penyu selama proses transportasi dapat diminimalkan, sehingga meningkatkan tingkat keberhasilan penetasan. Pemantauan teratur terhadap kondisi lingkungan sarang buatan, termasuk suhu, pH, dan kelembaban, juga penting untuk meningkatkan persentase penetasan.